Twelve-month results of the EverFlex stent in the superficial femoral artery - Diehl, Steffen J.; Gerblich, Felix; Jochum, Susanne; Huck, Kurt; Keese, Michael; Schönberg, Stefan; Sadick, Maliha (Journal of vascular and interventional radiology, 2012)
Purpose To evaluate the clinical efficacy of EverFlex stents (length, 6-20 cm) for the treatment of peripheral artery disease (PAD) in the superficial femoral artery (SFA). Material and Methods Over a period of 18 months, 56 SFA lesions in 53 patients were treated with an EverFlex stent. The following parameters were documented before the intervention, immediately afterward, and 12 months later: clinical stage, ankle-brachial index, and peak systolic velocity ratio (PSVR). The primary study endpoint was the primary patency rate after 12 months (defined as a PSVR < 2.5). Results In 18% of the 56 lesions, complete occlusions were present. Mean lesion length was 9.4 cm ± 5.3, and mean stent length was 12.6 cm ± 5.6. Of the 53 patients enrolled in the study, a 12-month follow-up was performed in 46. The primary patency rate after 12 months was 71.7%. In-stent restenosis or occlusion occurred in 13 patients. Compared with the total study group, the mean stent length in these 13 patients was greater (14.0 cm ± 7.3) and the incidence of de novo lesions was lower. In the patient group with stents less than 10 cm in length (n = 24), six patients (25%) required a repeat intervention, compared with seven patients (32%) in the group with stents longer than 12 cm. Conclusions Although the primary patency rate associated with the EverFlex stent is comparable to those in published data, the present results demonstrate a higher percentage of in-stent stenoses in patients in whom longer SFA stents were implanted.